A Story of Six Rivers : History, Culture and Ecology. - Coates, Peter A., 1957- (Reaktion Books, 2013)
Many of the world's major cities sprang up on the banks of rivers. Used for water, food, irrigation, transportation, and power, rivers sustain life and connect the world together, but most of us think of them simply as waterways that must be crossed on the way to another place. Using four European and two North American rivers as examples, A Story of Six Rivers considers the place of rivers in our world and emphasizes the inextricable links between history, culture, and ecology. Peter Coates explores six rivers, chosen as examples of the types of rivers found on the planet: the Danube, the sec.